Postural ability reflects the athletic skill level of surfers - Paillard, T.; Margnes, E.; Portet, M.; Breucq, A. (European Journal of Applied Physiology, 2011)
This work analyses surfers` postural control and their use of visual information in static (stable) and dynamic (unstable) postures according to their level of competition. Two groups of healthy surfers were investigated: a group of local level surfers (LOC) (n = 8) and a group of national/international level surfers (NIN) (n = 9). Posture was assessed by measuring the centre of foot pressure with a force platform for 50 s with stable support and for 25 s with unstable support (sagittal or frontal plane). The tests were completed with the eyes open (the subjects looked at a fixed level target at a distance of 2 m) and closed (they kept their gaze in a straight-ahead direction). Results showed that the contribution of vision in postural maintenance, with unstable support was less important in the NIN surfers than in the LOC surfers and that the NIN surfers had better postural control than the LOC surfers. Firstly, the results suggest that expert surfers could shift the sensorimotor dominance from vision to proprioception for postural maintenance. Secondly, there is a relationship between the postural ability and the competition level of surfers. These observations are likely to induce new prospects of training for surfers.